Strategic Governance Models for Scaling Clean Energy Startups in Emerging Economies: A Multi‑Stakeholder Systems Perspective - Lakhwani, Tejinder Singh (Clean Energy Technologies, 2025)
This study proposes a strategic governance framework to accelerate the scalable deployment of clean energy startups in emerging economies. Startups in solar, hydrogen, storage, and smart grid technologies play a vital role in advancing energy transitions. However, in regions such as India, Nigeria, and Brazil, these ventures face systemic barriers including fragmented policies, ϐinancing gaps, and limited institutional coordination. This research integrates stakeholder ecosystem mapping, multi‑level governance theory, and innovation helix models with simulation‑based scenario analysis to address these challenges. Using System Dynamics (SD) and Agent‑Based Modeling (ABM), the study evaluates three governance scenarios: centralized, decentralized, and public–private partnership (PPP) across key performance indicators: startup survival rate, scaling velocity, policy responsiveness, and stakeholder alignment. Case insights inform the modeling logic and highlight trade‑offs across governance types. Findings suggest that PPP‑based models offer the most balanced performance, combining scalability with institutional adaptability, while decentralized models support local innovation but require stronger systemic integration. Centralized governance, though stable, risks stifling entrepreneurship. This research contributes to a simulation‑informed governance framework that can guide clean energy policy design, startup ecosystem development, and adaptive regulation in resource‑constrained settings. It also provides a transferable foundation for future empirical studies and potential application to climate‑tech entrepreneurship and carbon credit systems.